PELAKSANAAN INOVASI DI BIDANG ADMINISTRASI KEPENDUDUKAN KOTA PAYAKUMBUH - Febri Yanti; Geovani Meiwanda (Cross-border, 2022)
Population administration is a series of activities to organize and issue documents through population registration, civil registration, and management of population administration information. The existence of innovation can improve the quality of public services to the community. The innovation "Puber Anak Melania" is a product created by the Department of Population and Civil Registration (DISDUKCAPIL) of Payakumbuh City in collaboration with the Public Health Center, Special Mother and Child Hospital (RSKIA) and the Indonesian Midwives Association (IBI) Payakumbuh City. The existence of Melania's Puberty innovation makes it easier for the community, faster in managing population administration documents in the city of Payakumbuh. The method used in this research is descriptive qualitative. Data collection techniques were obtained from the results of observations and interviews. The theoretical concept used in this research is the theory of Haryani and Yanartin in Muluk regarding the Typology of Innovation through Process Innovation. This study aims to determine the process of implementing the innovation "Puber Anak Melania" in Payakumbuh City. In accordance with the process of implementing the innovation, "Puber Anak Melania" really helps the community in managing their Population Administration Documents, but there are still problems such as limited human resources.